Vaccination with SARS-CoV-2 inactivated vaccines reduced the risk of anxiety and depression in a population majored by health care workers during the recent omicron variant outbreak - Zhao, Hong; Yu, Xia; Ye, Wenyi; Wang, Runzhu; Sheng, Jifang; Shi, Yu (Frontiers in Psychology, 2022)
Background The mental health status of the population majored by health care workers in China during the omicron variant outbreak remains unknown. Furthermore, the effect of COVID-19-inactivated vaccines on mental health is yet to be investigated. Methods A cross-sectional, online survey study was conducted from 12–20 April, 2022. The prevalence of symptoms of depression and anxiety were evaluated using the Hospital Anxiety and Depression Scale. Results Responses from a total of 1,387 participants were analyzed, 39.7% of which reported symptoms of mental health illness. The incidence of anxiety (30.4% vs. 48.4%, p < 0.001) and depression (27.1% vs. 46.3%, p < 0.001) decreased with COVID-19 inactivated vaccination. From multivariate analysis, living in Shanghai (anxiety: Odds ratio [OR]: 1.58, 95% confidence interval [CI]: 1.14–2.19, p = 0.006; depression: OR: 1.61, 95% CI: 1.16–2.25, p = 0.005), with a mental illness (anxiety: OR: 8.97, 95% CI: 1.01–79.56, p = 0.049; depression: OR: 9.32, 95% CI: 1.06–82.30, p = 0.045) increased the incidence of anxiety and depression. Elderly participants (anxiety: OR: 0.986, 95% CI: 0.975–0.997, p = 0.012; depression: OR: 0.976, 95% CI: 0.965–0.987, p < 0.001) who had been vaccinated against COVID-19 (anxiety: OR: 0.49, 95% CI: 0.32–0.75, p = 0.001; depression: OR: 0.45, 95% CI: 0.29–0.69, p < 0.001) had decreased incidences of anxiety and depression. Conclusion Our findings increase the awareness of the high incidence of mental health illness symptoms during the omicron variant outbreak despite previous experiences with the COVID-19 pandemic, and vaccination is suggested to reduce the risk of anxiety and depression.